How to Learn About Users and Understand Their Needs? User Experience, Mental Models and Research at Public Administration Websites - Herendy, Csilla (Socialiniai tyrimai, 2018)
About the research question: in the business world, companies increasingly tend to create their websites and apps by conducting exhaustive simultaneous or preliminary research and testing. Surfaces developed in this way are easy to use and understand, and they meet the explicit and implicit needs and expectations of the users. This in turn generates new expectations, that is, citizens need public administration sites to be usable and easy to understand at the same time. They want to be able to search for information, do administrative tasks and carry out other transactions in a straightforward manner (Béres and Zsák, 2007).In the meantime, it is a well known fact that citizens have a problem with orienting themselves on public administration websites in most countries. The interpretation of the information architecture and wording cause difficulty, a lot of things are not found in places where the user would look, and so on. However, if the surface of public administration sites is cumbersome, navigation is complicated, the expressions used there are difficult to understand, citizens will be annoyed, and choose personal administration with a bad feeling. This does not favor the spread of e-government, while, according to the eEurope action plans, public administration should be able to offer complex electronic public services that meet up to date standards of quality, content and functionality.The paper explores the possible backgrounds of the above problems, and presents methods for developing online public administration web surfaces in such a way the results meet the explicit and implicit expectations of users after all.The author gives real answers to the following questions:• How can public administration websites be more simple and straightforward to use?• How can web surfaces be tested, and in which phase of developing is it best to do this?• What kinds of known, tried methods are available for this, and when have they been used?• How did those who “did well” do it?In order to answer the above questions, the paper also presents some case studies, websites developed by governments and cities that specifically kept in mind the explicit expectations, values and points of view of users, and these needs were taken into account during development.Method of the research: following the thorough desk research, the author conducted and complemented the exploration with on site, personal and telephone interviews as well as e-mail communications. The presented examples are based on the author’s research going on since 2009.Main results, conclusion: The examples presented in the study aim to support the point that as well as all other websites, public administrations sites also need to or should be made with continuous testing during development, including the study of mental models (even if this was not a stated explicit need during the development).The presented examples demonstrate that sites that were systematically assessed through preliminary research and testing during development, and the finished page is also continuously developed, meet the expectations of users much better than those where this was not the case (see, for example, Herendy, 2015), and the subsequent studies of the author also confirm this.During the development of the studied sites, designers and developers conducted the following types of research, among others:• Analyzing web analytics, e.g. Google Analytics, in order to learn about the prior and present behavior and needs of the users;• Preparing online survey research, and analyzing the results in order to map the needs of users;• Workshops for designing the information architecture;• Card sorting tests to support the design of the information architecture;• A/B tests, which help developers pick the design that is easier and simpler to use from two options;• Preparing wireframes and prototypes, testing them with members of the target group;• Collecting feedback from users.The British gov.uk site can be an outstanding example to follow for all public administration organs, as it was designed with the use of nearly all the excellent testing and development methods: starting with learning about the needs of users, followed by A / B testing and preparing a prototype. They paid attention to optimizing color coding, the simplest possible presentation of everything, ease of use, iteration, and accessibility. They got to know existing mental models and stuck to them, they coordinated the adjustment of contrast, color, typography, icons, style, sound effects and visual metaphors.The British gov.uk site is also outstanding because it is not just about the government creating and continuously developing and shaping a web surface, but also teaches anyone interested in how they can create this kind of surface themselves, or at least one that meets such high standards.The presented examples represent the state of the sites in the period between 2012 and 2017. Some of the surfaces have been further developed in the meantime, and some were completely restructured.With a view to the harmful development practices that can be observed sometimes – not only in Hungary worldwide – (the development process is poorly planned, it involves no testing or testing is poorly implemented, authentic UX and research experts are not consulted, developments are often made in-house (which tends to happen due to the lack of information, rather than by bad intentions)), the presented examples are still of interest in 2017. This is especially true if we consider the testing and development methods that have been used smoothly for the past 5-10 years.